Basic approaches to psychological counseling of family relations - Mushkevych, Myroslava (Psychological Prospects Journal, 2022)
Purpose. The definition of the essence of psychological counseling, which is interpreted as a system of professional activity of a psychologist, as a purposeful process, represented by techniques and methods aimed at researching and interpreting individual and interpersonal characteristics of family members to create optimal conditions for development, adaptation and self-realization of each individual and family as a whole.Methods. A procedure for psychological counseling of families has been developed, the general methodology of which is based on the leading ideas of a systems approach, in which special emphasis is placed on the integrity of the system, in which any changes in one subsystem necessarily affect all other subsystems and the system as a whole. The presented algorithm of the psycho-counseling procedure consists of two stages and the process begins with the psychodiagnostic stage - the application of the projective method "Family Drawing" is implemented. The second stage - psychoconsultative analysis of the results and selection and implementation of the routes towards positive changes in interpersonal relationships.Results. The classification of gender differentiation of expression of personal factors of family members is presented, the difference of personal and family functioning in representatives with different family status, level of functioning is proved. It was found that as a result of psychoconsultative influence the number of family members with a well-established attitude to positive perception and acceptance of a partner or other members of the nuclear family, reflected position and willingness to generate constructive space of marital and family relationships, to cultivate "healthy" family values and attitudes, implementation of constructive role patterns of family functioning has increased.Conclusions. Psychological counseling is an important component of psychological assistance to families using a systematic approach to the family, aimed at developing positive changes in family values, family roles, attitudes, marital and interpersonal relationships and attitudes, acceptance of partners or other members of the nuclear family.
Keywords: nuclear family, family system, marriage subsystem, psychodiagnostics, psycho-counseling.